Pancreatic functions in adolescents with beta thalassemia major could predict cardiac and hepatic iron loading: relation to T2-star (T2*) magnetic resonance imaging. Issue 3 (March 2016) - Mokhtar, Galila M; Ibrahim, Wafaa E; Elbarbary, Nancy S; Matter, Randa M; Ibrahim, Ahmed S; Sayed, Safa M
Abstract : The aim of this study is to assess the correlation between cardiac and hepatic T2* MRI findings with the endocrine and exocrine pancreatic functions in known patients with β-thalassaemia major (β-TM). A total of 50 adolescent patients with β-TM and 44 healthy controls were investigated via: serum amylase, lipase, triglyceride index, oral glucose tolerance test and T2* MRI, to assess iron content in the heart and liver. Diabetes was found in 20%, and 40% of patients had impaired fasting glucose (IFG). Cardiac T2* was less than 10 ms in 22% indicating heavy load with iron in cardiac tissues. There was a significant decrease in median serum amylase (63.5 vs 87.5 IU/L, p=0.003) and lipase (63 vs 90 IU/L, p=0.017) among patients in comparison with the control group. Patients with β-TM and diabetes had lower serum amylase (32 vs 68 IU/L), lipase (28 vs 79 IU/L), cardiac and hepatic T2* MRI (7 vs 25.5 ms; 3 vs 6 ms, p<0.001 for all) than those without diabetes. Similar results were found among patients with IFG when compared with others (p<0.001 for all). Cardiac and hepatic T2* were inversely correlated to triglyceride index (r=−0.376, p=0.014 and r=−0.475, p=0.001, respectively) and positively correlated to amylase (r=0.791 and r=0.790) and lipase (r=0.784 and r=0.783; p<0.001 for all). The endocrine and exocrine pancreatic functions might become an equivalent predictor to cardiac and hepatic iron overload, especially in countries where MRI is not available or where it is expensive. The early occurrence of these abnormalities warrants more intensive chelation therapy.